Adhesive, injectable, and ROS-responsive hybrid polyvinyl alcohol (PVA) hydrogel co-delivers metformin and fibroblast growth factor 21 (FGF21) for enhanced diabetic wound repair - Zhu, Hong; Xu, Jie; Zhao, Min; Luo, Hangqi; Lin, Minjie; Luo, Yuting; Li, Yuan; He, Huacheng; Wu, Jiang (Frontiers in Bioengineering and Biotechnology, 2022)
As conventional treatments for diabetic wounds often fail to achieve rapid satisfactory healing, the development of effective strategies to accelerate diabetic wound repair is highly demanded. Herein, fibroblast growth factor 21 (FGF21) and metformin co-loaded multifunctional polyvinyl alcohol (PVA) hydrogel was fabricated for improved diabetic wound healing. The in vitro result proved that the hydrogel was adhesive, injectable and particularly it could scavenge reactive oxygen species (ROSs), while the in vivo data demonstrated that the hydrogel could promote angiogenesis by recruiting endothelial progenitor cells (EPCs) through upregulation of Ang-1. Both ROSs removal and EPCs recruitment finally resulted in the enhanced diabetic wound healing. This work opened a strategy approach to diabetic wound management through combining biological macromolecules and small chemical molecules together using one promising environmental modulating drug delivery system.